2019
DOI: 10.1093/qje/qjz023
|View full text |Cite
|
Sign up to set email alerts
|

What do Workplace Wellness Programs do? Evidence from the Illinois Workplace Wellness Study*

Abstract: Workplace wellness programs cover over 50 million U.S. workers and are intended to reduce medical spending, increase productivity, and improve well-being. Yet limited evidence exists to support these claims. We designed and implemented a comprehensive workplace wellness program for a large employer and randomly assigned program eligibility and financial incentives at the individual level for nearly 5,000 employees. We find strong patterns of selection: during the year prior to the intervention, program partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
225
3
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 278 publications
(258 citation statements)
references
References 44 publications
9
225
3
3
Order By: Relevance
“…Section 4 relates these health improvements to health care cost and utilization. With a simple difference‐in‐differences specification, we do not find clear evidence that program participation is associated with lower health care cost, at least over the first 4 years of the program, and this finding is consistent with the results of Jones et al (), who find similar results in a randomized control trial in a similar context. In fact, we find some evidence for higher health care cost over the first 2 years.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Section 4 relates these health improvements to health care cost and utilization. With a simple difference‐in‐differences specification, we do not find clear evidence that program participation is associated with lower health care cost, at least over the first 4 years of the program, and this finding is consistent with the results of Jones et al (), who find similar results in a randomized control trial in a similar context. In fact, we find some evidence for higher health care cost over the first 2 years.…”
Section: Introductionsupporting
confidence: 90%
“…In one specification, we compare the passing rate of program participants between those new participants and individuals who have been participating in the program for several years, and we find that longer program participation is associated with significant and meaningful improvements in screening results, especially for men.Section 4 relates these health improvements to health care cost and utilization. With a simple difference-in-differences specification, we do not find clear evidence that program participation is associated with lower health care cost, at least over the first 4 years of the program, and this finding is consistent with the results of Jones et al (2018), who find similar results in a randomized control trial in a similar context. In fact, we find some evidence for higher health care cost over the first 2 years.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…This method relies on a bootstrap resampling technique that simulates data under the null hypothesis. It calculates the probability of observing results as extreme as the ones estimated given the correlational structure and underlying distributions of the data, and the number of tests run within each family of outcomes (Jones, Molitor, & Reif, 2018). Using this more conservative approach, the adjusted p-value for the treatment impact on violent-crime arrests for males is p = 0.073.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…As a counterpoint to these and other positive findings (see next paragraph), a more widely publicized report by the RAND corporation (Mattke et al., , ) concluded that wellness programs have limited effectiveness (cf. Jones, Molitor, & Reif, ). The RAND report further concludes that previous studies suggesting cost effectiveness had significant methodological shortcomings (Baicker et al., ).…”
Section: Part 1—introductionmentioning
confidence: 99%